The Perspective of Information Systems in Digitalized Enterprises - Ruiz Segura, John Phillips (2010)
This article reviews the impact of information systems in enterprises in general. Many national and international companies carry the trauma of having had serious problems for the implementation of a computerized information system. “The benefits of investments in information technology will be if the companies do not consider the costs of the change in the organization associated with a new or do not do that these changes are effective”. (Laudon 2004, 426-427). Therefore it is desirable to understand the problems associated with information systems.